STUDI ANALISIS FONDASI TIANG PADA TANAH EKSPANSIF DI DAERAH CIKARANG DAN KARAWANG - Reynaldi Andika; Andryan Suhendra (JMTS: Jurnal Mitra Teknik Sipil, 2023)
Expansive soils contain the mineral montmorillonite, which is highly susceptible to changes in moisture content and can easily expand or shrink and subsequently damage the foundation or building above it. Foundation design is important in the construction of a structure and must be properly considered to strengthen the structure. In this study, we want to know the value of changes in the bearing capacity of the pile foundation during soil expansion and shrinkage. And also examine the value of bearing capacity and foundation settlement when there is a change in groundwater level. Because the clay soil shrinks and expands, the negative skin friction and heave analysis of the piles is also carried out. The results of the analysis were obtained using 2D finite element applications. Based on the results of the analysis of the bearing capacity value and soil settlement, the fluctuation of the groundwater table elevation is one of the influential factors, at low elevations the bearing capacity value is greater and the soil settlement is smaller, then at high elevations the opposite will occur. Meanwhile, when the soil is drained, it will produce a greater bearing capacity value than when it is undrained. Abstrak Tanah ekspansif mengandung mineral montmorilonit, yaitu mineral yang sangat rentan oleh perubahan kadar air sehingga mudah mengalami muai atau susut lalu selanjutnya merusak fondasi atau bangunan di atasnya. Perancangan fondasi adalah hal yang penting dalam pembuatan struktur dan harus dipertimbangkan secara tepat untuk memperkuat struktur. Dalam penelitian ini, kami ingin mengetahui nilai perubahan daya dukung fondasi tiang saat terjadi muai susut tanah. Dan juga meneliti nilai daya dukung dan penurunan fondasi ketika terjadi perubahan muka air tanah. Karena tanah lempung mengalami susut dan kembang, maka dilakukan juga analisis negative skin friction dan heave pada tiang pancang Hasil analisis didapatkan menggunakan aplikasi elemen hingga 2D. Berdasarkan hasil analisis nilai daya dukung dan penurunan tanah bahwa fluktuasi elevasi muka air tanah merupakan salah satu faktor yang berpengaruh, pada elevasi rendah nilai daya dukung semakin besar dan penurunan tanah semakin kecil maka pada elevasi tinggi akan terjadi kebalikannya. Sedangkan pada saat tanah dalam kondisi drained akan menghasilkan nilai daya dukung yang lebih besar daripada saat kondisi undrained.